Environmental Determinants of Cardiovascular Disease - Bhatnagar, Aruni (Circulation research, 2017)
Many features of the environment have been found to exert an important influence on cardiovascular disease (CVD) risk, progression, and severity. Changes in the environment because of migration to different geographic locations, modifications in lifestyle choices, and shifts in social policies and cultural practices alter CVD risk, even in the absence of genetic changes. Nevertheless, the cumulative impact of the environment on CVD risk has been difficult to assess and the mechanisms by which some environment factors influence CVD remain obscure. Human environments are complex, and their natural, social, and personal domains are highly variable because of diversity in human ecosystems, evolutionary histories, social structures, and individual choices. Accumulating evidence supports the notion that ecological features such as the diurnal cycles of light and day, sunlight exposure, seasons, and geographic characteristics of the natural environment such as altitude, latitude, and greenspaces are important determinants of cardiovascular health and CVD risk. In highly developed societies, the influence of the natural environment is moderated by the physical characteristics of the social environments such as the built environment and pollution, as well as by socioeconomic status and social networks. These attributes of the social environment shape lifestyle choices that significantly modify CVD risk. An understanding of how different domains of the environment, individually and collectively, affect CVD risk could lead to a better appraisal of CVD and aid in the development of new preventive and therapeutic strategies to limit the increasingly high global burden of heart disease and stroke.